2019
DOI: 10.13102/sociobiology.v66i3.4264
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Ants (Hymenoptera: Formicidae) in a Sub-Montane and Sub-Tropical Cityscape of Northeastern Mexico

Abstract: - The role of urban ecosystems in maintaining biodiversity and ecosystem services is highly variable because of the heterogeneity of habitats in human-use landscapes. We analyzed ant diversity in a sub-montane and sub-tropical urban area of northeastern Mexico to determine the conservation value of this cityscape. Ants were collected in 16 across the cityscape, including spaces at the periphery and urban center, during the rainy season (August to October) of 2015. To capture ants, eight trap traps were install… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Not surprisingly, some studies have assessed the role of urbanization in ant communities. Although it was often detected an overall negative effect of urbanization on ant diversity (e.g., Thompson and McLachlan 2007;Uno et al 2010;Dáttilo et al 2011;García-Martínez et al 2019), this is not a consensus (Savitha et al 2008;Cross et al 2016). Moreover, previous studies have suggested that grounddwelling and arboreal ants respond differently to urban habitat changes (Estrada et al 2014;Santiago et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, some studies have assessed the role of urbanization in ant communities. Although it was often detected an overall negative effect of urbanization on ant diversity (e.g., Thompson and McLachlan 2007;Uno et al 2010;Dáttilo et al 2011;García-Martínez et al 2019), this is not a consensus (Savitha et al 2008;Cross et al 2016). Moreover, previous studies have suggested that grounddwelling and arboreal ants respond differently to urban habitat changes (Estrada et al 2014;Santiago et al 2018).…”
Section: Introductionmentioning
confidence: 99%